Targeting Resident Memory T Cells for Cancer Immunotherapy - Blanc, Charlotte; Hans, Sophie; Tran, Thi; Granier, Clemence; Saldman, Antonin; Anson, Marie; Oudard, Stephane; Tartour, Eric (Frontiers in Immunology, 2018)
A novel population of memory CD8+T cells have been identified based on their phenotype (CD103, CD69) and on their local tissue residency without recirculating in the blood. These cells have been implicated in protective immune response against pathogens in both animal models and humans. Their role in cancer is just emerging as a key player in tumor immunosurveillance. Many properties of these cells suggested that it could control tumor growth : i) they respond much faster to reexposure to cognate antigen, when compared with circulating memory cells. ii) they express high levels of cytotoxic molecules iii) they are enriched in tumor specific T cells in close contact with tumor cells. TRM are present in many human cancers and are associated with a good clinical outcome independently of the infiltration of CD8+T cells. It has been recently shown that the efficacy of cancer vaccines depends on their ability to elicit TRM. In adoptive cell therapy, the transfer of cells with the ability to establish TRM at the tumor site correlated with the potency of this approach. Interestingly, TRM express checkpoint inhibitors and preliminary data showed that they could expand early during anti-PD-1 treatment and be considered as a surrogate marker of response to immunotherapy. Mucosal route of immunization, local signal to favor the recruitment of TRM or the targeting of subpopulations of dendritic cells with the ability to elicit them constitute some cues to better expand these cells for the success of cancer immunotherapy